MiR-574-5p: A Circulating Marker of Thoracic Aortic Aneurysm - Adeline Boileau (International Journal of Molecular Sciences, 2019)
Thoracic aortic aneurysm (TAA) can lead to fatal complications such as aortic dissection. Since aneurysm dimension poorly predicts dissection risk, microRNAs (miRNAs) may be useful to diagnose or risk stratify TAA patients. We aim to identify miRNAs associated with TAA pathogenesis and that are possibly able to improve TAA diagnosis. MiRNA microarray experiments of aortic media tissue samples from 19 TAA patients and 19 controls allowed identifying 232 differentially expressed miRNAs. Using interaction networks between these miRNAs and 690 genes associated with TAA, we identified miR-574-5p as a potential contributor of TAA pathogenesis. Interestingly, miR-574-5p was significantly down-regulated in the TAA tissue compared to the controls, but was up-regulated in serum samples from a separate group of 28 TAA patients compared to 20 controls (p < 0.001). MiR-574-5p serum levels discriminated TAA patients from controls with an area under the receiver operating characteristic curve of 0.87. In the Fbn1C1041G/+ mouse model, miR-574-5p was down-regulated in aortic tissue compared to wild-type (p < 0.05), and up-regulated in plasma extracellular vesicles from Fbn1C1041G/+ mice compared to wild-type mice (p < 0.05). Furthermore, in vascular smooth muscle cells, angiotensin II appears to induce miR-574-5p secretion in extracellular vesicles. In conclusion, miR-574-5p is associated with TAA pathogenesis and may help in diagnosing this disease.